Integrating Intralingual and Extralingual Cotext in Educational Pragmatic Learning - ., Pranowo (KnE Social Sciences, 2018)
Humans do not learn from experience but rather from the reflection of experiences that have been felt. Therefore, educational pragmatic learning, which has not developed in Indonesian language learning, needs to be reflected in order to become a new experience that can benefit both oneself and others in the future. One of the important things with respect to one’s experience is communicating by understanding the cotext. However, the cotext itself between one expert and another has a different understanding of several cotexts, such as (1) the linguistic cotext, (2) the social cotext, (3) the cotext of the situation, and (4) the cultural cotext. Language learning involving cotexts is categorized as educational pragmatic learning. It is designed by integrating both intralingual and extralingual cotexts so that language learning in addition to being linguistic can also be cotextual. Keywords: cotext, educational pragmatics, intralingual/extralingual